Synthesis of an Aryl-Semicarbazone-Based Cu(II) Complex for DNA and BSA Interaction and Anti-Cancer Activity against Human Cervix Uteri Carcinoma - Maity R.; Manna B.; Maity S.; Jana K.; Maity T.; Afzal M.; Sepay N.; Samanta B.C. (My University, 2025)
The current study provides an in-depth analysis of the biological properties of a Cu(II) complex (C22H24Cu2N6O10) obtained from an aryl-semicarbazone ligand derived (L) from the condensation of 2,4-dihydroxy acetophenone and semicarbazide. The binding behavior of this complex with calf thymus DNA (CT-DNA) and bovine serum albumin (BSA) protein was explored using a combination of experimental and theoretical approaches. The results suggest that the complex binds with CT-DNA via a partial intercalation, and hydrophobic interaction. However, the complex binds to BSA protein predominantly through hydrogen bonding or van der Waals interactions rather than hydrophobic interactions. The molecular docking methodology was carried out to substantiate the experimental finding. Furthermore, the in vitro cytotoxicity study was conducted on human cervix uteri carcinoma (SiHa cancerous cell) lines upon exposure to the complex, and the findings reveal a considerable decrease in cell viability, when compared to the control. Overall, this study provides a comprehensive understanding of the biological potential of the Cu(II) complex and its potential as an anti-cancer agent. © 2024 by the authors.